Flame-retardant polyester fiber based on modified hydroxyapatite and preparation method thereof
By modifying the surface of hydroxyapatite monophenyl phosphate and preparing through melt blending, the problem of degradation of mechanical properties of flame retardant polyester fibers when improving flame retardant properties is solved, and efficient and stable flame retardant properties and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202510202868.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
While the existing flame retardant polyester fibers have difficulty maintaining mechanical properties while improving flame retardant properties, and their compatibility with the polyester matrix is poor, resulting in insufficient dispersion.
The surface modification of hydroxyapatite is performed by monophenyl phosphate to form modified hydroxyapatite, and then the flame retardant polyester fiber is prepared by melt blending.
The flame retardant and mechanical properties of flame retardant polyester fibers have been improved, the limit oxygen index has been increased to 29.0%-30.7%, the flame retardant level has reached V0 level, no melt droplets have been generated, and the fracture strength is not less than 3.0cN/dtex.
Smart Images

Figure CN119685966A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fibers, and in particular relates to a flame-retardant polyester fiber based on modified hydroxyapatite and a preparation method thereof. Background Art
[0002] Polyester fiber has been widely used in the textile field due to its excellent mechanical properties (such as high strength and high modulus), excellent wrinkle resistance, easy washing and quick drying, and good processing performance, and its output continues to grow. However, the limiting oxygen index of conventional polyester fiber is only 20%, which is a flammable fiber, and it is easy to drop at high temperatures, greatly increasing the risk of fire. With the increasing requirements for safety, the regulations and standards for the flame retardant properties of fabrics are becoming more and more stringent. Therefore, it is particularly urgent to develop polyester fibers with high-efficiency flame retardant properties.
[0003] As an important functional fiber, flame-retardant polyester fiber has been widely used in daily home textile products such as curtains, carpets, sofas, and pajamas. However, existing flame-retardant polyester fibers still face many challenges. In particular, how to further improve their flame-retardant effect while ensuring their stable performance and harmlessness to the human body and the environment is one of the current research focuses. In order to improve the flame retardant properties of polyester fibers, researchers have tried to add different nano flame retardants by blending. Among them, hydroxyapatite, as a potential natural mineral, has attracted more and more attention. Hydroxyapatite is the main component of animal bones and teeth, with a high phosphorus content and rich calcium ions. These characteristics make it play an important role in increasing the speed and amount of carbon layer formation, thereby helping to improve the flame retardant and anti-drip properties of polyester fibers.
[0004] However, although the flame retardant properties of hydroxyapatite have great potential in theory, its compatibility with the polyester matrix is poor, resulting in insufficient dispersion in the polyester matrix. This uneven dispersion makes the polyester fiber with the addition of hydroxyapatite show poor flame retardant properties in practical applications, and has a significant negative impact on the mechanical properties (such as strength) of the polyester fiber. Therefore, the development of efficient, stable and performance-balancing modification methods has become the key to improving the performance of flame-retardant polyester fibers.
[0005] Invention patent CN104845025A discloses a highly efficient modified ABS composite material using nano-hydroxyapatite loaded composite flame retardant and a preparation method thereof. During the preparation process of the composite material, nano-ATO, tricresyl phosphate, melamine cyanurate and other raw materials are used as environmentally friendly composite flame retardant synergists, and they are infiltrated and loaded into nano-hydroxyapatite under high pressure conditions, and then the flame retardant is added to the ABS material; however, nano-ATO, tricresyl phosphate, melamine cyanurate and other raw materials cannot form a strong bond with nano-hydroxyapatite, and the flame retardant still has poor compatibility with polyester fibers, making it difficult to effectively improve the flame retardant properties of polyester fibers.
[0006] Wu Zhihao et al. (Preparation and performance study of flame-retardant modified recycled polyester fiber by synergistic flame retardant of phosphorus flame retardant and α-zirconium phosphate. Proceedings of the 3rd International Symposium on Flame Retardant Materials and Technologies, 2014: 214-215.) prepared flame-retardant recycled polyester (RPET) fiber by melt blending of phosphorus flame retardant (FRP) and α-zirconium phosphate (α-ZrP). The limiting oxygen index of the recycled polyester fiber increased, but its mechanical properties were greatly damaged. This is because the nanoparticle α-zirconium phosphate has poor compatibility with polyester fiber and poor dispersion in polyester fiber, resulting in significant damage to the mechanical properties of the modified recycled polyester fiber.
[0007] Therefore, it is of great significance to modify hydroxyapatite for the preparation of flame-retardant polyester fibers. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a flame-retardant polyester fiber based on modified hydroxyapatite and a preparation method thereof. First, hydroxyapatite is surface-modified with monophenyl phosphate to obtain modified hydroxyapatite, and then the modified hydroxyapatite is used to prepare the flame-retardant polyester fiber based on the modified hydroxyapatite by melt blending.
[0009] The first object of the present invention is to provide a method for preparing a flame retardant polyester fiber based on modified hydroxyapatite, comprising the following steps: S1, adding hydroxyapatite to a monophenyl phosphate solution for ultrasonic treatment and heating reaction to obtain modified hydroxyapatite; S2, granulating the modified hydroxyapatite and polyester powder described in S1 to obtain a flame retardant polyester masterbatch; S3, spinning the flame-retardant polyester masterbatch and polyester chips described in S2 to obtain the flame-retardant polyester fiber based on modified hydroxyapatite.
[0010] In one embodiment of the present invention, in S1, the monophenyl phosphate solution includes monophenyl phosphate and ethanol; the mass fraction of monophenyl phosphate in the monophenyl phosphate solution is 10%-20%; hydroxyapatite has good dispersibility in ethanol, which helps the modification of hydroxyapatite by monophenyl phosphate.
[0011] In one embodiment of the present invention, in S1, the mass ratio of monophenyl phosphate to hydroxyapatite is 1:(3-4), and a small amount of monophenyl phosphate is used to coat hydroxyapatite, so that the surface of hydroxyapatite is rich in aromatic benzene rings, thereby improving its compatibility with polyester fibers and its dispersion performance in polyester fibers.
[0012] In one embodiment of the present invention, in S1, the power of the ultrasonic treatment is 200W-500W, and the time is 30min-50min.
[0013] In one embodiment of the present invention, in S1, the heating reaction is carried out at a temperature of 50°C-60°C and for a time of 2h-3h.
[0014] In one embodiment of the present invention, before S2, it also includes a step of drying the modified hydroxyapatite and polyester powder, the drying temperature of the modified hydroxyapatite is 60°C-70°C, and the drying time is 8h-10h; the drying temperature of the polyester powder is 125°C-135°C, and the time is 9h-11h.
[0015] In one embodiment of the present invention, in S2, the granulation is performed by melt blending, extrusion molding, cooling and pelletizing through a twin-screw extruder; the granulation temperature is 260°C-270°C. If the processing temperature is too low, the modified hydroxyapatite and polyester powder cannot be mixed evenly, which is not conducive to granulation. If the temperature is too high, it will cause energy waste.
[0016] In one embodiment of the present invention, in S2, the mass fraction of modified hydroxyapatite in the flame retardant polyester masterbatch is 15%-20%.
[0017] In one embodiment of the present invention, before S3, the step of drying the flame retardant polyester masterbatch and the polyester chips is also included, wherein the drying is performed by pre-crystallization at 90°C-100°C for 3h-4h, and then drying at 125°C-135°C for 10h-14h to ensure that the final moisture content of the flame retardant polyester masterbatch and the polyester chips is less than 100ppm.
[0018] In one embodiment of the present invention, in S3, the spinning is carried out by a melt spinning machine, followed by oiling, pre-stretching, winding, and stretching; the spinning process parameters are: speed of 2600m / min-2800m / min, temperature of 270℃-280℃, and traction ratio of 1.5-2.
[0019] In one embodiment of the present invention, in S3, the mass fraction of the flame retardant polyester masterbatch in the flame retardant polyester fiber based on modified hydroxyapatite is 12%-16%.
[0020] The second object of the present invention is to provide a flame retardant polyester fiber based on modified hydroxyapatite prepared by the preparation method.
[0021] In one embodiment of the present invention, the flame retardant polyester fiber based on modified hydroxyapatite has a limiting oxygen index of 29.0%-30.7%, a flame retardant grade of V0, no droplets are generated, and a breaking strength of not less than 3.0 cN / dtex.
[0022] The technical solution of the present invention has the following advantages over the prior art: (1) The preparation method of the present invention uses monophenyl phosphate to modify the surface of hydroxyapatite. On the one hand, the surface of hydroxyapatite is rich in calcium ions (Ca 2+ ), the phosphate groups in monophenyl phosphate can form a stable calcium-phosphate complex with the calcium ions on the surface of hydroxyapatite through coordination, so that monophenyl phosphate is firmly adsorbed on the surface of hydroxyapatite. On the other hand, the benzene ring structure in the monophenyl phosphate molecule can form affinity with the aromatic groups in polyester through π-π stacking interaction, which significantly improves the compatibility between modified hydroxyapatite and polyester fiber. This interaction enhances the dispersion performance of modified hydroxyapatite in polyester fiber, thereby overcoming the original compatibility problem and improving the processing performance and mechanical properties of polyester fiber.
[0023] (2) The hydroxyapatite in the flame-retardant polyester fiber based on modified hydroxyapatite described in the present invention is rich in phosphorus and calcium ions, while monophenyl phosphate not only contains abundant phosphorus, but also contains an aromatic carbon-forming agent with good thermal stability. The synergistic effect between phosphate groups, calcium ions and aromatic groups plays a key role in the flame retardant process. Phosphate groups and calcium ions can form a protective carbon layer during pyrolysis to inhibit the combustion of polyester fibers; while aromatic groups can promote carbonization, further enhancing the flame retardant effect and anti-dripping effect. The synergistic effect of the three makes the modified hydroxyapatite composite material show higher efficiency and stability in flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 This is a schematic diagram of the structure of the modified hydroxyapatite of Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0026] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0027] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0028] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0029] In the present invention, unless otherwise specified, the monophenyl phosphate solution used in the examples of the present invention is prepared by dissolving monophenyl phosphate in ethanol.
[0030] In the present invention, unless otherwise specified, the polyester powder and polyester chips used in the embodiments of the present invention are purchased from Yizheng Chemical Fiber with a brand name of FG650.
[0031] In the present invention, unless otherwise specified, the hydroxyapatite powder used in the examples of the present invention is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a brand name of H684219 and a particle size of about 60 nm-80 nm. Example 1
[0032] The flame-retardant polyester fiber based on modified hydroxyapatite and the preparation method thereof of this embodiment specifically include the following steps: S1. First, hydroxyapatite powder was slowly added into a 15% monophenyl phosphate solution, and then ultrasonically treated at 350W for 40min, and then the solution was heated to 55°C and stirred for 2.5h. Finally, the excess solvent was removed by rotary evaporation, and the modified hydroxyapatite was obtained after washing with deionized water and drying. Figure 1); wherein the mass ratio of monophenyl phosphate to hydroxyapatite is 1:3.5; S2, the modified hydroxyapatite was vacuum dried at 65°C for 9h; the polyester powder was vacuum dried at 130°C for 10h, and after mixing, it was melt blended, extruded, cooled and pelletized by a twin-screw extruder. The temperature of the twin-screw extruder was 265°C to obtain a flame-retardant polyester masterbatch with a modified hydroxyapatite mass fraction of 18%; S3, the flame retardant polyester masterbatch and the polyester chips were pre-crystallized in a 95°C blast oven for 3.5 hours, and then dried at 130°C for 12 hours, so that the final moisture content of the flame retardant polyester masterbatch and the polyester chips was less than 100 ppm. After mixing, they were spun through a melt spinning machine, cooled and oiled, pre-stretched, wound, and stretched. The speed of the melt spinning machine was 2700 m / min, the temperature was 275°C, and the traction ratio was 1.8, to obtain a flame retardant polyester fiber based on modified hydroxyapatite with a mass fraction of 14% of the flame retardant polyester masterbatch. Example 2
[0033] The flame-retardant polyester fiber based on modified hydroxyapatite and the preparation method thereof of this embodiment specifically include the following steps: S1. First, hydroxyapatite powder is slowly added into a 10% by mass monophenyl phosphate solution, and then ultrasonically treated at 200W for 50 minutes, and then the solution is heated to 50°C and stirred for 3 hours, and finally the excess solvent is removed by rotary evaporation, and the solution is washed with deionized water and dried to obtain modified hydroxyapatite; wherein the mass ratio of monophenyl phosphate to hydroxyapatite is 1:3; S2, the modified hydroxyapatite was vacuum dried at 60°C for 10 hours; the polyester powder was vacuum dried at 125°C for 11 hours, and after mixing, it was melt blended, extruded, cooled and pelletized by a twin-screw extruder. The temperature of the twin-screw extruder was 260°C to obtain a flame-retardant polyester masterbatch with a modified hydroxyapatite mass fraction of 15%; S3, the flame retardant polyester masterbatch and the polyester chips were pre-crystallized in a 90°C blast oven for 4 hours, and then continued to be dried at 125°C for 14 hours, so that the final moisture content of the flame retardant polyester masterbatch and the polyester chips was less than 100 ppm. After mixing, they were spun through a melt spinning machine, cooled and oiled, pre-stretched, wound, and stretched. The speed of the melt spinning machine was 2600 m / min, the temperature was 270°C, and the traction ratio was 1.5, to obtain a flame retardant polyester fiber based on modified hydroxyapatite with a mass fraction of 12% of the flame retardant polyester masterbatch. Example 3
[0034] The flame-retardant polyester fiber based on modified hydroxyapatite and the preparation method thereof of this embodiment specifically include the following steps: S1. First, hydroxyapatite powder is slowly added into a monophenyl phosphate solution with a mass fraction of 20%, and then ultrasonically treated at 500W for 30 minutes, and then the solution is heated to 60°C and stirred for reaction for 2 hours, and finally the excess solvent is removed by rotary evaporation, and the solution is washed with deionized water and dried to obtain modified hydroxyapatite; wherein the mass ratio of monophenyl phosphate to hydroxyapatite is 1:4; S2, the modified hydroxyapatite is vacuum dried at 70°C for 8h; the polyester powder is vacuum dried at 135°C for 9h, and after mixing, it is melt-blended, extruded, cooled and pelletized by a twin-screw extruder, and the temperature of the twin-screw extruder is 270°C to obtain a flame-retardant polyester masterbatch with a modified hydroxyapatite mass fraction of 20%; S3, the flame retardant polyester masterbatch and the polyester chips were pre-crystallized in a 100°C blast oven for 3 hours, and then dried at 135°C for 10 hours, so that the final moisture content of the flame retardant polyester masterbatch and the polyester chips was less than 100 ppm. After mixing, they were spun through a melt spinning machine, cooled and oiled, pre-stretched, wound and stretched. The speed of the melt spinning machine was 2800 m / min, the temperature was 280°C, and the pulling ratio was 2, so as to obtain a flame retardant polyester fiber based on modified hydroxyapatite with a mass fraction of 16% of the flame retardant polyester masterbatch. Comparative Example 1
[0035] Basically the same as Example 1, except that monophenyl phosphate is replaced by phosphoric acid. Comparative Example 2
[0036] The same as Example 1, except that monophenyl phosphate is replaced by phenol. Comparative Example 3
[0037] The method is basically the same as Example 1, except that monophenyl phosphate is not used for modification. Comparative Example 4
[0038] Basically the same as Example 1, except that hydroxyapatite is replaced by calcium carbonate. Comparative Example 5
[0039] Basically the same as Example 1, except that hydroxyapatite is replaced by calcium hydroxide. Comparative Example 6
[0040] The method is basically the same as Example 1, except that modified hydroxyapatite is not used for modification. Test Case
[0041] The physical properties of the flame-retardant polyester fibers (modified polyester fibers) based on modified hydroxyapatite and the unmodified polyester fibers prepared in Examples 1-3 and Comparative Examples 1-6 were tested: Limiting oxygen index: Refer to FZ / T 50017-2011 "Test method for flame retardancy of polyester fiber - oxygen index method" to test the limiting oxygen index of modified polyester fiber and unmodified polyester fiber; Burning test: Refer to the UL94 vertical burning standard to test the droplet generation and flame retardancy of modified polyester fiber and unmodified polyester fiber; Breaking strength: Refer to GB / T 14344-2022 "Test method for tensile properties of chemical fiber filaments" to test the breaking strength of modified polyester fiber and unmodified polyester fiber; Table 1 shows the relevant properties of the unmodified polyester fiber and the modified polyester fiber finally measured: Table 1
[0042] As can be seen from Table 1, the modified polyester fiber has a higher limiting oxygen index, no droplets are generated, the flame retardant grade is V0, the flame retardant performance is good, and the breaking strength is high, indicating that the modified hydroxyapatite and polyester fiber have good compatibility.
[0043] By comparing Example 1 and Comparative Example 1, it can be seen that when monophenyl phosphate is replaced by phosphoric acid, the flame retardant properties of the modified polyester fiber are reduced, no droplets are generated, but the breaking strength is significantly reduced. This is because the phosphoric acid coated on the surface of hydroxyapatite has poor compatibility with the polyester fiber, making it difficult for the modified hydroxyapatite to be evenly dispersed in the polyester fiber.
[0044] By comparing Example 1 and Comparative Example 2, it can be seen that when monophenyl phosphate is replaced by phenol, the flame retardant properties of the modified polyester fiber are reduced, molten droplets are generated, and the breaking strength is reduced. This is because the phosphate group in monophenyl phosphate has a synergistic flame retardant effect, and the phosphate group has a strong chelating ability with calcium ions, which makes the binding force between monophenyl phosphate and hydroxyapatite stronger.
[0045] Comparison of Example 1 and Comparative Example 3 shows that when monophenyl phosphate is not used for modification, the unmodified hydroxyapatite is difficult to be uniformly dispersed in the polyester fiber, resulting in significant damage to the mechanical properties of the polyester fiber and reduced flame retardancy.
[0046] By comparing Example 1 and Comparative Example 4, it can be seen that when hydroxyapatite is replaced by calcium carbonate, the flame retardant performance of the modified polyester fiber is reduced, droplets are generated, and the breaking strength is reduced. This is because the flame retardant efficiency of calcium carbonate is much lower than that of hydroxyapatite.
[0047] By comparing Example 1 and Comparative Example 5, it can be seen that when hydroxyapatite is replaced by calcium hydroxide, the flame retardant performance of the modified polyester fiber is reduced, droplets are generated, and the breaking strength is reduced. This is because the flame retardant efficiency of calcium hydroxide is much lower than that of hydroxyapatite.
[0048] By comparing Example 1 and Comparative Example 6, it can be seen that the limiting oxygen index of the polyester fiber without flame retardant modification is 20.1%, molten droplets are generated in the UL-94 vertical burning test, the flame retardant grade is NR, the molten droplets are serious, and the flame retardant performance is poor.
[0049] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing flame-retardant polyester fiber based on modified hydroxyapatite, characterized in that: The following steps are involved: S1, adding hydroxyapatite to a monophenyl phosphate solution for ultrasonic treatment and heating reaction to obtain modified hydroxyapatite; S2, granulating the modified hydroxyapatite and polyester powder described in S1 to obtain a flame retardant polyester masterbatch; S3, spinning the flame-retardant polyester masterbatch and polyester chips described in S2 to obtain the flame-retardant polyester fiber based on modified hydroxyapatite.
2. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S1, the monophenyl phosphate solution includes monophenyl phosphate and ethanol; the mass fraction of monophenyl phosphate in the monophenyl phosphate solution is 10%-20%.
3. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S1, the mass ratio of monophenyl phosphate to hydroxyapatite is 1:(3-4).
4. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S1, the power of the ultrasonic treatment is 200W-500W, and the time is 30min-50min.
5. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S1, the heating reaction temperature is 50°C-60°C, and the time is 2h-3h.
6. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S2, the granulation is performed by melt blending, extrusion molding, cooling and pelletizing through a twin-screw extruder; the granulation temperature is 260°C-270°C.
7. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S2, the mass fraction of modified hydroxyapatite in the flame retardant polyester masterbatch is 15%-20%.
8. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S3, the spinning is carried out by a melt spinning machine, followed by oiling after cooling, pre-stretching, winding, and stretching; the spinning process parameters are: speed of 2600m / min-2800m / min, temperature of 270℃-280℃, and traction ratio of 1.5-2.
9. The method for preparing flame-retardant polyester fiber based on modified hydroxyapatite according to claim 1, characterized in that: In S3, the mass fraction of the flame retardant polyester masterbatch in the flame retardant polyester fiber based on modified hydroxyapatite is 12%-16%.
10. Flame-retardant polyester fiber based on modified hydroxyapatite prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-efficiency improved ABS (Acrylonitrile Butadiene Styrene) composite material for loading composite flame retardant by using nano-hydroxyapatite and preparation method thereof
CN104845025A
Flame-retardant polycarbonate composition and preparation method thereof
CN101792585A
Melt stable and hydrolysis resistant compositions
CN104583290A
High-property flame-retardant composite material for automatic equipment and preparation method thereof
CN107828208A
High-strength textile fabric with flame-retardant effect and preparation method thereof
CN115305619A
Cited By
Multifunctional polyester fiber and preparation method thereof
CN119685967A
Multifunctional polyester fiber and preparation method thereof
CN119685967B